A Universal Approach to Anchoring Chromophores onto Magnetic Scaffold for Achieving Easily Recyclable Heterogeneous Photocatalytic Systems - Xuan Zhan; Yikun Wang; Chenyang Sun; Yuchen Fang; Lihua Huang; Zakir Ullah; Qiang Chen; Xuejing Wang; Zheng Xing; Gangfeng Ouyang (Advanced Science, 2025)
Abstract Photocatalysis based on chromophores such as porphyrin, coumarin, anthraquinone, and pyrene is a promising technology to achieve green synthesis of various high‐value chemicals, but the robust and non‐covalent immobilization of chromophores onto light‐inert scaffolds for industrialization‐oriented heterogeneous photocatalysis remains challenging. In this work, a simple and universal strategy is presented for preparing highly efficient and recyclable heterogeneous photocatalysts from chromophores, which is achieved via biotinylation of chromophore molecules and subsequent supramolecular binding of chromophore‐biotin dyads to streptavidin‐decorated magnetic beads. As an example, commercial magnetic beads modified by 5,10,15,20‐tetrakis(4‐aminophenyl) porphyrin not only possessed remarkable photocatalytic activities for the oxidative coupling of benzylamine derivatives and the oxidation of thioanisole derivatives with highest product yields of beyond 95% and turnover numbers approaching 10000, driven by photogenerated reactive oxygen species but also demonstrated impressive chemical stability and efficient recyclability via simple magnetic separation during 10 successive test cycles. The findings revealed in this work pave the way for advancing green synthesis of valuable organic compounds in the pharmaceutical industry, agricultural sector, etc., with rationally designed heterogeneous photocatalytic systems.